(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
Triple negative breast cancer (TNBC) has a more aggressive clinical course compared to other breast cancer subtypes. The presence of a triple negative receptor status causes the ineffectiveness of such types of targeted treatment as hormonal therapy and targeted therapy with Herceptin , in contrast to luminal and Her-2/ neu -positive tumors. In this regard, chemotherapy today remains the only accepted method of systemic treatment in this category of patients. Over the past few years, great advances have been made in the comprehensive treatment of TNBC. But, despite this, TN breast cancer remains one of the aggressive forms of malignant breast tumors with a high level of metastasis and low survival compared to other subtypes of breast cancer. The study conducted an IHC study of AR status in patients with TN breast cancer and, based on the results obtained, a mathematical model was created to determine its significance in predicting the outcome of the disease. Using regression -correlation analysis, it is possible to assess the prognostic value of AR expression in patients with breast cancer, followed by the calculation of an equation that makes it possible to make a forecast and determine the significance of the main parameters. The use of developed mathematical models, which include the most important predictive criteria, makes it possible with sufficiently high sensitivity and specificity to predict the outcome of the disease depending on the AR status in patients with TN BC